2021
DOI: 10.3390/sexes2030025
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Female Migrant Domestic Workers’ Experiences of and Responses to Work-Based Sexual Violence in Cyprus

Abstract: Domestic workers face increased risk for sexual harassment and assault in the workplace but are often reluctant to disclose abuse or seek retribution. We report on a study looking at migrant domestic workers’ responses to sexual violence, reasons behind their responses, and factors enhancing or diminishing vulnerability to abuse. We carried out qualitative, in-depth, individual and group interviews with 15 female domestic workers from the Philippines and Sri Lanka working in the Republic of Cyprus. Descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The low socio-economic status of these groups, precarious working conditions and language difficulties were the most common barriers identified in the current study and were related to lower standards of care or limited choice availability in the healthcare system. This does not come as a surprise and is consistent with emerging evidence from other research teams across countries [17][18][19][20][21][22]. A recent study published by Vazquez and colleagues [23] highlighted certain immigrants' sociodemographic characteristics as key barriers to effective care.…”
Section: Discussionsupporting
confidence: 80%
“…The low socio-economic status of these groups, precarious working conditions and language difficulties were the most common barriers identified in the current study and were related to lower standards of care or limited choice availability in the healthcare system. This does not come as a surprise and is consistent with emerging evidence from other research teams across countries [17][18][19][20][21][22]. A recent study published by Vazquez and colleagues [23] highlighted certain immigrants' sociodemographic characteristics as key barriers to effective care.…”
Section: Discussionsupporting
confidence: 80%
“…The lack of accommodation in general and particularly decent accommodation, was highlighted by the Kayayei in this study as a source of distress and anxiety. Previous studies have also reported that the Kayayei find it difficult to obtain affordable accommodation upon their arrival in their host cities ( 11 , 72 , 73 ). This reality forced many participants to find shelter in front of Kiosks with little or no security nor safety as they reported being attacked by armed robbers, sexual violence including abduction by predators.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic work puts housemaids in a highly disadvantaged position as it is one of the least protected sectors under labor law, in turn, worsens their vulnerability to sexual violence [ 13 16 ]. Most housemaids are obligated to attend their education on the night shift as they do not get the opportunity to continue their education on a regular program, which increases their vulnerability to sexual violence [ 6 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%